Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1002/cbf.1575
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of ascorbic acid on hepatotoxicity and oxidative stress caused by carbon tetrachloride in the liver of Wistar rats

Abstract: This study was planned to investigate the protective effect of l(+)-ascorbic acid (Vit C) on CCl(4)-induced hepatotoxicity and oxidative stress in the liver of Wistar rats (Rattus Norvegicus, strain Wistar). Twenty-four adult male Wistar rats were fed with standard rat chow diet for 10 days and randomly were divided into four groups of six each as follows: (1) control, (2) CCl(4), (3) "CCl(4) + Vit C", (4) Vit C groups. CCl(4) was applied to rats belonging to CCl(4) and "CCl(4) + Vit C" groups subcutaneously a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 35 publications
(36 reference statements)
2
28
0
1
Order By: Relevance
“…The results of the present experiment are in agreement with results obtained in other experimental studies [21][22][23][24]. For example, the study of Cemek et al demonstrates that the administration of CCl 4 leads to severe acute liver affection in rats, revealed by significant increase of AST and ALT serum levels.…”
Section: Discussionsupporting
confidence: 93%
“…The results of the present experiment are in agreement with results obtained in other experimental studies [21][22][23][24]. For example, the study of Cemek et al demonstrates that the administration of CCl 4 leads to severe acute liver affection in rats, revealed by significant increase of AST and ALT serum levels.…”
Section: Discussionsupporting
confidence: 93%
“…Elevation in levels of GOT, GPT and LDH in response to CCl 4 is the signs of liver injury because these enzymes are located in the cytoplasm and escape out into the circulation when the cells are attacked [22,23]. In our study, serious hepatocyte injury was observed after exposed to 8 mM CCl 4 as shown by the increases of GOT, GPT and LDH level in the supernatant.…”
Section: Discussionmentioning
confidence: 48%
“…At the level of cellular structure vitamin C showed improvement in mitochondrial structure and function. These improvements were mainly via antioxidative role of ascorbic acid [43,44] .…”
Section: Discussionmentioning
confidence: 99%